(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Vaginal discharge is a common gynaecological problem worldwide. It is a common presentation of different gynaecological diseases. Objective: The aim of the study was to find out the aetiological factors responsible for vaginal discharge among the women presented with cervical pathology. Methodology: This cross sectional study was carried out in patients complaining of vaginal discharge attending at Gynaecology department (GOPD) in Dhaka Medical College Hospital (DMCH), Dhaka from March’2006 to October’2006. Required tests were carried out in the Department of Microbiology and Department of Pathology at Dhaka Medical College, Dhaka. Data were obtained by history taking, physical examination and relevant investigations. Results: Cervical pathology was associated in 64.0% of patients complaining of vaginal discharge. Out of these, most common are cervicitis (48.0%) carcinoma of cervix (8.0%) cervical erosion (4.0%) endocervical polyp (2.0%) and old cervical tear (2.0%). Other associated aetiologies of abnormal vaginal discharge were bacterial vaginosis (12.0%) candidiasis (10.0%) trichomoniasis (10.0%). Conclusion: Vaginal discharge is a manifestation of many cervical pathology including carcinoma. Therefore, proper evaluation is needed in all patients complaining of vaginal discharge before treatment. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16203 J Shaheed Suhrawardy Med Coll, 2013;5(1):31-34